Analisis Perencanaan Pembangkit Listrik Tenaga Surya (PLTS) dengan Sistem On Grid di Gedung Kantor Pelabuhan PT. Pupuk Kalimantan Timur - Wahyu Syahrir (Syntax Idea)
To support the energy transition and maintain the Green Port title, it is necessary to design a Solar Power Plant (PLTS) in the PT Pupuk Kalimantan Timur Port Office Building. In designing a PLTS system, a design analysis is needed that is appropriate to the roof capacity or roof area available on the building and the potential for solar radiation at that location. The stages carried out include selecting a PLTS system, selecting PLTS components, creating a PLTS design using the HelioScope simulator, and calculating investment feasibility. The results of this research show that there is potential for electricity production of 109.8 MWh per year with the construction of PLTS in the PT Pupuk Kalimantan Timur Port Office Building. The appropriate PLTS installation design is PLTS with an On-Grid system, consisting of 158 solar panels with a capacity of 540 Wp (Seraphim 540 BMA HV) and 1 inverter with a capacity of 100 kW (SUN 200–100KTL–M1). The installed capacity of PLTS is 85.3 kWp with a Performance Ratio of 79.6% and specific energy of 1,286.8 kWh/kWp. Investment in the construction of PLTS in the PT Pupuk Kalimantan Timur port office building is feasible with an investment value of IDR 872,515,500,-, IRR of 11.18% (IRR > WACC) and NPV of IDR 8,789,894.50 (NPV>0). The estimated return on capital can be carried out in the 7th year. It is hoped that this research can be a reference for the design and calculation of installing PLTS in the PT Pupuk Kalimantan Timur Port Office Building.